Pengaruh Brand Image Dan Promosi Terhadap Keputusan Pemakaian Indihome Di PT Telkom Indonesia (Persero) Tbk Area IV Jateng Kota Semarang Dimasa Pandemi Covid-19 : Studi Pada Pelanggan Indihome Di Kecamatan Mijen - Nadia Dwi Irmadiani (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
The purpose of a purchasing decision is a process where consumers recognize their problems, seek information about certain products or brands and evaluate whether each of these alternatives can solve their problems which then leads to a purchase decision. Through brand image and promotion, it is expected to be able to attract customers in making purchasing decisions. This type of research is explanatory, which focuses on analyzing the effect of brand image and promotion variables on purchasing decisions. The population in this study were residents of Mijen District, Semarang City. While the sample was taken 3% of the total population of 1792 IndiHome users, namely 60 respondents. The sampling technique uses area random sampling. In collecting data using questionnaires, documentation and observation. Before statistical analysis, displayed in mono tables and cross tables, then analyzed using multiple regression analysis. From the research that has been done, it results that the brand image in Mijen District is in the high category (80.97%), promotional variables are in the medium category with (56.96%), and purchasing decisions are in the high category (91.45%). Through hypothesis testing carried out using product moment correlation techniques with the research results being r_ (x_1 y) = 0.304 after being consulted with the r table at the 5% confidence level (0.254) with N = 60, it can be said that r count is greater than r table. Thus it can be concluded that there is a strong influence between brand image on purchasing decisions in Mijen District. While r_(x_2 y) = 0.635 after being consulted with the r table at the 5% confidence level (0.254) with N = 60, it can be said that r count is greater than r table. Thus it can be concluded that there is a strong influence between promotion on purchasing decisions in Mijen District. While r_(x_(1x_2)y) = 0.638 after being consulted with the r table at the 5% confidence level (0.254) with N = 60, it can be said that r count is greater than r table. Thus it can be concluded that there is a strong influence between brand image and promotion on purchasing decisions in Mijen District.